Peran Perfilman Islami dalam Membentuk Integrasi dan Toleransi Beragama di Indonesia di Era Digital - Suci Sulistiawati; Lilis Sulistiawati; Wina Sumiati (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Inter-religious tolerance is defined as an attitude of accepting, recognizing, respecting and appreciating the beliefs of others. The emergence of conflict is often caused by individualistic feelings that still arise in social relationships. This article aims to review in depth the role of Islamic cinema in presenting narratives that promote peace, harmony, and mutual understanding between religious communities in Indonesia. This analysis uses a qualitative analysis approach, the data collected contains data quotations from literature studies, books, films, articles, and literature. The results showed that there are 3 values of tolerance contained in the movie “Tanda Tanya”. First, it leads to efforts to provide freedom. Second, recognizing everyone's rights. Third, respecting other people's beliefs.